Can capital markets be harnessed for the financing of small and medium-sized enterprises (SMEs) in low- and middle-income countries? - Sommer, Christoph (IDOS policy brief, 2024)
SMEs are key to development, as they provide livelihoods and jobs for the majority of people in LMICs. Yet, their development is often hampered by constrained access to finance. SMEs mostly depend on bank loans for external finance. However, these have been insufficient to overcome SMEs’ financing constraints, especially in LMICs, such that it seems pertinent to explore other financing sources. The World Bank and OECD have repeatedly pointed to capital markets (e.g. Thompson et al., 2018; World Bank, 2020a). Hence, this policy brief explores the role of capital markets for SME finance in LMICs. Numerous challenges, both on the supply and demand sides, impede SMEs’ involvement with capital markets. SMEs struggle with the costs of issuing securities, reporting and corporate governance requirements and, in the case of equity, with concerns about dilution of ownership. Investors on the demand side are discouraged by imperfect information and limited exit options. Consequently, SMEs hardly use equity or market-based debt, especially in LMICs. However, capital markets can have an indirect positive effect on SME finance: Several financial instruments (e.g. securitisation, equity capital for banks) exploit the respective comparative advantages of banks (information-related activities) and markets (liquidity), and create interactions with benefit flows from markets to banks and vice versa, which result in their complementarity and co-evolution. Specifically, capital market development is associated with increases in bank lending, in particular to smaller and riskier firms (Sommer, 2024; Song & Thakor, 2010). Yet, this is not necessarily the first-best option to mitigate SMEs’ financing constraints, since it often takes decade-long reforms to create suitable conditions for capital markets. This has the following implications for policymaking: • Policymakers need to tailor their decisions to the most promising ways of fostering SME finance to local contexts. While SME promotion may involve capital market development in some middle-income countries, this is still way off for many LMICs, as it may take strenuous institutional and structural reforms over a prolonged period to create an environment for thriving capital markets. • Policymakers should foster non-traditional instruments to provide SMEs with direct access to capital market financing. Receivables and lending platforms are especially promising for LMICs and can be promoted through specialised regulatory frameworks, information and capacity-building, as well as co-investments and tax incentives. • Policymakers should scale up policies to improve SMEs’ access to loans; this serves both as an immediate response to SMEs’ financing constraints and as a complement to policies to ensure that banks’ increased lending activities (spillovers from capital market development) can (also) be channelled towards SMEs. Depending on country-specific bottlenecks, this may include addressing well-known problems in SME lending through the establishment of credit bureaus and registries as well as moveable asset registries; strengthening contract enforcement and insolvency laws; and implementing a regulatory framework conducive to digitalisation.